(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article discusses the clinical features, diagnostic challenges, and treatment approaches of IBS in this age group. Irritable bowel syndrome (IBS) is a functional disorder characterized by impaired intestinal motility and hypersensitivity to internal and external factors. In adolescence, this syndrome is associated with many comorbid conditions, including allergic diseases, psychoemotional disorders, and metabolic syndrome.